In search of retention: volunteers in a Brazilian NGO - Aquino, Marcos Aurelio Gomes de; Cavalcante, Carlos Eduardo; Caldas, Patrícia Trindade; Mendes, Josiete da Silva (Revista de Administração da UFSM, 2020)
This study aims to analyse the motives that lead current and prospective volunteers to engage in volunteer activity at the Cidade Viva Foundation in the city of João Pessoa, state of Paraíba, Brazil. To that end, the model proposed by Cavalcante (2016) is employed to describe volunteers’ motivational profiles at different points in time: their prior expectations, at the moment when they join the organization, and when they quit. The methodology chosen includes descriptive research and analysis of data collected through questionnaire-based interviews with volunteers at the Cidade Viva Foundation using inferential statistics (Student’s t test and Bonferroni test -ANOVA). Among the most significant findings is the predominance of the altruistic profile, followed by the social justice profile, the learning profile, the affiliation profile, and the selfish profile, both in prior expectations and at the moment of joining. Similarly, the selfish profile was least common.